Vesiculobullous autoimmune diseases with oral mucosa manifestations: retrospective and follow-up study - Rani Iani Costa GONÇALO; Mara Luana Batista SEVERO; Ana Miryam Costa de MEDEIROS; Patrícia Teixeira de OLIVEIRA; Éricka Janine Dantas Da SILVEIRA (Faculdade São Leopoldo Mandic, 2018)
Objective: To conduct a retrospective study on a series of cases of PV and BMMP with manifestations in the oral cavity in order to ascertain prevalence, sociodemographic characteristics, diagnostic maneuvers, treatment and follow-up. Methods: This is a retrospective, descriptive study in which clinical data were collected from the medical records of all cases of PV and BMMP registered and diagnosed, between 1995 and 2015, in the Oral Diagnostic Service of the UFRN Department of Dentistry. Results: The mean age of the total sample (n = 36) was 41.64, with females the most frequent (n = 26; 72.22%) and the cheek mucosa being the site most affected (n = 20; 27.40%). Eight patients (22.22%), including 5 cases of PV and 3 BMMP, were clinically reevaluated. All patients exhibited lesions at the time of follow-up. Prednisone (n=7; 87.5%) and clobetasol propionate (n=8, 100%) were the most widely used drugs in the systemic and topical treatment, respectively. The follow-up period ranged from 5 months to 5 years. Conclusion: The clinical profile of patients in this study was similar to that evidenced in the literature. However, it was found that the oral lesions were more resistant to the treatment used on the patients evaluated.